2011
DOI: 10.1371/journal.pone.0021457
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide Renders Transgenic Mice Expressing Human Serum Amyloid P Component Sensitive to Shiga Toxin 2

Abstract: Transgenic C57BL/6 mice expressing human serum amyloid P component (HuSAP) are resistant to Shiga toxin 2 (Stx2) at dosages that are lethal in HuSAP-negative wild-type mice. However, it is well established that Stx2 initiates extra-intestinal complications such as the haemolytic-uremic syndrome despite the presence of HuSAP in human sera. We now demonstrate that co-administering purified Escherichia coli O55 lipopolysaccharide (LPS), at a dosage of 300 ng/g body weight, to HuSAP-transgenic mice increases their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…8). In this modified model, transgenic (HuSAP-tg) mice are pre-exposed to LPS to induce a sub-acute state of inflammation that ablates the confounding effects of HuSAP on toxicity of Stx2a (45). HuSAP-tg mice (C57BL/6-Tg(APSC)1Imeg) treated intraperitoneally with a lethal dose of Stx2a (225 pg/g mouse) combined with E. coli O55 LPS (300 ng/g mouse) were immediately given increasing intravenously concentrations of PolyBAIT-P k ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…8). In this modified model, transgenic (HuSAP-tg) mice are pre-exposed to LPS to induce a sub-acute state of inflammation that ablates the confounding effects of HuSAP on toxicity of Stx2a (45). HuSAP-tg mice (C57BL/6-Tg(APSC)1Imeg) treated intraperitoneally with a lethal dose of Stx2a (225 pg/g mouse) combined with E. coli O55 LPS (300 ng/g mouse) were immediately given increasing intravenously concentrations of PolyBAIT-P k ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…HuSAP binds to and neutralizes Stx2a in the absence of glycan ligands, and based on the observation that HuSAP transgenic mice were completely resistant to Stx2a, this interaction was initially considered to be of potential therapeutic value in preventing Stx2a-initiated HUS in E. coli O157:H7-infected patients (44). However, it was subsequently revealed that there was no correlation between the circulating concentration of HuSAP and the risk for developing HUS in humans (45).…”
Section: Discussionmentioning
confidence: 99%
“…CYP7A1 is involved in drug metabolism and synthesis of bile acid and steroids from cholesterol within liver tissue. Conversion of cholesterol into bile acid is controlled by this protein and is the main process of removing cholesterol from the body [43]. Removal of cholesterol from the body is important to the overall homeostatic state of organism.…”
Section: Discussionmentioning
confidence: 99%
“…HuSAP producing transgenic mice were also found to be resistant to Stx2 [52]. However, introduction of lipopolysaccharide renders transgenic mice expressing HuSAP sensitive to Stx2 [53]. Bundle et al have since shown that HuSAP transgenic mice pre-exposed to LPS and challenged with a lethal amount of Stx2 (225 pg/g body weight) were moderately protected (~60%) by PolyBait (100 μg/g body weight) [54].…”
Section: Accepted Manuscriptmentioning
confidence: 99%